The Religious Heritage in the Modern Bahraini Arabic Poetic Text “Sheikh Ibrahim bin Mohammed Al Khalifa” is a model - Amen, Raed waleed (Dirasat: Human and Social Sciences, 2025)
Objectives This research aims to examine the phenomenon of religious heritage in modern Bahraini Arabic poetry, with a focus on the poet Sheikh Ibrahim bin Mohammed Al Khalifa as a case study. The study seeks to explore how this heritage enriches the creative poetic experience and sheds light on its theoretical and practical aspects. The theoretical aspect clarifies the concept of religious heritage and its employment in poetic texts, while the practical aspect analyzes Sheikh Ibrahim bin Mohammed Al Khalifa’s use of religious heritage, highlighting his ability to blend the past and present in a novel manner. Methods: The study adopts a descriptive-analytical approach due to its effectiveness in deconstructing and analyzing the phenomenon into its fundamental components and elements of the creative process. Results: The research concludes with significant findings, most notably the illumination of Sheikh Ibrahim bin Mohammed Al Khalifa’s poetic experience. The study reveals his adept engagement with heritage, utilizing its rich cultural, linguistic, and aesthetic elements in a profound and multifaceted manner. Conclusion: Sheikh Ibrahim bin Mohammed Al Khalifa skillfully employed religious and historical heritage in his poetic compositions, relying on an objective framework that aligns with his emotions, philosophy, vision, and artistic sensibility. This precise utilization of heritage reflects a deep and structured relationship within the creative process between the poet and his art.